Peptides derived from hookworm anti-inflammatory proteins suppress inducible colitis in mice and inflammatory cytokine production by human cells - Cobos, Claudia; Bansal, Paramjit S.; Wilson, David T.; Jones, Linda; Zhao, Guangzu; Field, Matthew A.; Eichenberger, Ramon M.; Pickering, Darren A.; Ryan, Rachael Y. M.; Ratnatunga, Champa N.; Miles, John J.; Ruscher, Roland; et al. (Frontiers in Medicine, 2022)
A decline in the prevalence of parasites such as hookworms appears to be correlated with the rise in non-communicable inflammatory conditions in people from high- and middle-income countries. This correlation has led to studies that have identified proteins produced by hookworms that can suppress inflammatory bowel disease (IBD) and asthma in animal models. Hookworms secrete a family of abundant netrin-domain containing proteins referred to as AIPs (Anti-Inflammatory Proteins), but there is no information on the structure-function relationships. Here we have applied a downsizing approach to the hookworm AIPs to derive peptides of 20 residues or less, some of which display anti-inflammatory effects when co-cultured with human peripheral blood mononuclear cells and oral therapeutic activity in a chemically-induced mouse model of acute colitis. Our results indicate that a conserved helical region is responsible, at least in part, for the anti-inflammatory effects. This helical region has potential in the design of improved leads for treating IBD and possibly other inflammatory conditions.